Influence of trunk model DOF on shoulder kinematics in javelin throwing - a case study - Roemer, K.; Köhler, H.-P.; Witt, M. (ISBS Proceedings Archive (Michigan), 2018)
A case study was conducted to clarify the influence of different body-models and modelling approaches on shoulder joint kinematics. Therefore, a single subject performed a javelin throw. The recorded movement was analyzed using two different modeling approaches using two different body models each. Results from the two different body models are highly comparable, while comparability of model approach specific results depend on the movement direction. Source of the difference between movement directions may be the model specific location of center of rotation in the shoulder joint.